Le sport et l`esthétique du corps dans les pays totalitaires - Wolf-Fédida, M.; Radtchenko-Draillard, S. (Movement & Sport Sciences - Science & Motricité, 2018)
The aim of this article is to study the impact of the totalitarian ideologies on sports practices. According to our hypothesis, sports activities in the totalitarian states interact with collective actions combining ambivalent contributions of the crowd with an oscillation between different psychosocial tendencies like competition, cooperation, obedience, identification, etc. Our comparative analysis of three states (Germany, Italy and USSR) shows the importance of sports as being an aesthetic product for the human body as well as a generator of the image of the "new world" necessary for the promotion of their ideologies. Majorly, the nature of unifying is more likely as being the opposite of the borderline pathology synonym for individualists and modern way of life.